PARAMETRIC STUDY OF NATURAL CONVECTIVE AND RADIATIVE HEAT TRANSFER IN INCLINED CYLINDRICAL ANNULI - Hadi Al-Hafidh, Manal; S. Safwat, Lina (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
The unsteady state laminar mixed convection and radiation through inclined cylindrical annulus is investigated numerically. The two heat transfer mechanisms of convection and radiation are treated independently and simultaneously. The outer cylinder was kept at a constant temperature while the inner cylinder was heated with constant heat flux. The study involved numerical solution of the governing equations which are continuity, momentum and energy equations using finite difference method (FDM), where the body fitted coordinate system (BFC) was used to generate the grid mesh for computational plane. A computer program (Fortran 90) was built to calculate the bulk Nusselt number (Nub) after reaching steady state condition for fluid Prandtl number fixed at (Pr =0.7) (for air) with radius ratio ( =1.5, 2.6, 5.0), Rayleigh number (0≤Ra≤103),Reynolds number (50≤Re≤2000), dimensionless heat generation (0≤Q≤10), Conduction-Radiation parameter (0≤N≤10), optical thickness (0 ≤ t  ≤ 10) and different annulus inclination with horizontal plane (0°≤δ≤90°). For the range of parameters considered, results show that radiation enhance heat transfer. It is also indicated in the results that Nu increase with the increasing of inclination angle δ, Ra, Re, and Q. The correlation equations are concluded to describe the radiation effect. Comparison of the result with the previous work shows a good agreement.